(untitled) (Discourse of Law and Administration, 2023)
Terms such as heroism, heroic, supererogative acts, professional duty, ethos and moral injury applied to health care professionals (HCPs) when performing their work during the COVID-19 pandemic have been expanded to include new ethical and legal contexts over the last two years. The aim of the article is to analyze the above-mentioned terms and to try to determine how their meanings have evolved based on the ethos of HCPs (ethical and legal regulations) and reports on problems connected with the coronavirus pandemic.